1998
DOI: 10.1080/004982598239768
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolism of darifenacin in the mouse, rat, dog and man

Abstract: 1. Following intravenous administration to animals at 2.5 mg/kg, darifenacin exhibited terminal plasma half-lifes < 2 h due to high plasma clearance (with respect to blood flow) and volumes of distribution greater than total body water. 2. Following oral administration to animals at doses > 4 mg/kg there was evidence of saturation of clearance since oral AUCs exceeded those expected from the high plasma clearances. In addition, terminal plasma half-lifes were greater than those estimated from intravenous admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 3 publications
1
33
0
Order By: Relevance
“…Several pharmacological studies have demonstrated that darifenacin has no Ca 2+ -channel antagonist action [11,14,16]. In addition, it has been shown to exhibit favorable selectivity for the bladder compared with the salivary glands and heart in vivo, while atropine is nonselective [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacological studies have demonstrated that darifenacin has no Ca 2+ -channel antagonist action [11,14,16]. In addition, it has been shown to exhibit favorable selectivity for the bladder compared with the salivary glands and heart in vivo, while atropine is nonselective [14].…”
Section: Introductionmentioning
confidence: 99%
“…UK-148,993, UK-73,689, and UK-88,862 are the three main circulating darifenacin metabolites, of which only UK-148,993 is said to have signifi cant antimuscarinic activity. UK-148,993 is formed primarily through CYP2D6 and CYP3A4 [44]. Because only small amounts of unchanged darifenacin is excreted via urine, most of the metabolites formed are inactive.…”
Section: Darifenacinmentioning
confidence: 99%
“…MAA: methacrylic acid 4-VP: 4-vinylpyridine [14] under clinical development for urinary incontinence [ 15,16]. In either case, the lower limit of quantification is often determined not by the limit of detection (at, say, a signal-to-noise ratio of 5) but by interference by co-eluting endogenous material.…”
Section: Introductionmentioning
confidence: 99%